The importance of recognizing the protection of personal data as a fundamental right (Research, Society and Development, 2022)
The Brazilian Federal Constitution of 1988, through Constitutional Amendment 115/2022, began to include in its text an fundamental right to the protection of personal data. The amendment completes the concept of the right to data protection, beyond mere protection of privacy, but as a fundamental right linked to the protection of personality, making its relevance and growing presence in social relations even more explicit. In this perspective, the present text aims to present and discuss some of the most relevant aspects concerning the fundamental right to the protection of personal data, its justification, its content, associated legal positions, the related protection duties, its horizontal effectiveness, as well as as its importance and legal certainty.